Multicomponent Polymerization of Alkynes, Sulfonyl Azide, and Iminophosphorane at Room Temperature for the Synthesis of Hyperbranched Poly(phosphorus amidine)s - Xu, Liguo; Yang, Kou; Hu, Rongrong; Tang, Ben Zhong (Synlett, 2018)
The construction of functional hyperbranched polymers with unique topological structures and distinct properties remains a great challenge. Multicomponent polymerization, as a fascinating polymer synthetic approach, has proved to be a powerful tool for the synthesis of polymers with diverse structures and multifunctionalities, which is a great advantage for the preparation of hyperbranched polymers. In this work, a multicomponent polymerization of alkynes, sulfonyl azide, and iminophosphorane is utilized for the construction of heteroatom-rich hyperbranched poly(phosphorus amidine)s with different topological structures and fluorescence response toward platinum group metal ions.
Keywords: hyperbranched polymer; multicomponent polymerization; alkynes; poly(phosphorus amidine)s; luminescence